Calculation:

Consider, the equation, \(\displaystyle{y}={16}—{3}{x}\),

To compute x-intercept, put \(\displaystyle{y}={0}\).

\(\displaystyle{0}={16}-{3}{x}\)

Add —16,to both the sides, this gives,

\(\displaystyle{0}-{16}={16}-{3}{x}-{16}\)

\(\displaystyle-{16}=-{3}{x}\)

Divide both sides of the equation by -3,

\(\displaystyle{\frac{{-{16}}}{{-{3}}}}={\frac{{-{3}{x}}}{{-{3}}}}\)

\(\displaystyle{x}={\frac{{{16}}}{{{3}}}}\)

So, the x-intercept is \(\displaystyle{\left({\frac{{{16}}}{{{3}}}},{0}\right)}\).

To compute y -intercept, put \(\displaystyle{x}={0}\),

\(\displaystyle{y}={16}-{3}{\left({0}\right)}\)

\(\displaystyle{y}={16}\)

So, the y-intercept is(0,16).

Hence, the x and y intercepts of \(\displaystyle{y}={16}-{3}{x}\) are \(\displaystyle{\left({\frac{{{16}}}{{{3}}}},{0}\right)}\) and(0,16),respectively.

Consider, the equation, \(\displaystyle{y}={16}—{3}{x}\),

To compute x-intercept, put \(\displaystyle{y}={0}\).

\(\displaystyle{0}={16}-{3}{x}\)

Add —16,to both the sides, this gives,

\(\displaystyle{0}-{16}={16}-{3}{x}-{16}\)

\(\displaystyle-{16}=-{3}{x}\)

Divide both sides of the equation by -3,

\(\displaystyle{\frac{{-{16}}}{{-{3}}}}={\frac{{-{3}{x}}}{{-{3}}}}\)

\(\displaystyle{x}={\frac{{{16}}}{{{3}}}}\)

So, the x-intercept is \(\displaystyle{\left({\frac{{{16}}}{{{3}}}},{0}\right)}\).

To compute y -intercept, put \(\displaystyle{x}={0}\),

\(\displaystyle{y}={16}-{3}{\left({0}\right)}\)

\(\displaystyle{y}={16}\)

So, the y-intercept is(0,16).

Hence, the x and y intercepts of \(\displaystyle{y}={16}-{3}{x}\) are \(\displaystyle{\left({\frac{{{16}}}{{{3}}}},{0}\right)}\) and(0,16),respectively.